FAKTOR-FAKTOR YANG MEMPENGARUHI MANAJEMEN LABA PERUSAHAAN PUBLIK DI INDONESIA PADA TAHUN 2008 - Yanuar Nanok S.; Natasya Natasya; Brigitta Azaria Widadi3 (Journal of Applied Finance & Accounting, 2010)
Financial report are one of the measurement for company achivement and income is the easiest and one of the most usefull kriteria for company performance. One  alternative to make financial report look good for investor, usually company use income smoothing for window dressing. Using 219 company in Indonesian stock exchange at 2008, we can assume that size of the company, leverage, accounting public, and operating cash flow are the significant variabel to make manajemen create income smoothing. We can concluded, with good control, owners can push manajemen to create financial report more transparant.